Representation as politics: asserting a feminist ethic in ethnographic research. Issue 1 (2nd January 2021) - Leaney, Sarah; Webb, Rebecca
ABSTRACT: As ethnographers we are familiar with methodological debates problematising ethnography's inherited and inherent connections to ideas of authenticity commonly mobilised to legitimate modes of representation. In this paper, we engage with the post-structural philosophies of Jacques Rancière and Judith Butler, to argue that methodological tools of representation are always 'political' and as such shape the limitations of what can be known. In order to trace the overlapping methodological foundations which inform our ethnographic representations, we introduce three paradigmatic constructions of ethnography. By paying attention to the ways in which our ethnographic representations mark the perceptibility of educational practices and purposes, we assert a feminist ethic through the representation of the 'livable life' as a productive methodological provocation.